Kebun Buah Learning Media for Early Childhood Counting Ability - Despa Ayuni; Farida Agus Setiawati (LPPM Universitas Pahlawan Tuanku Tambusai, 2019)
Children aged 5-6 years have four types of tasks in counting ability, which are to distinguish between bigger and smaller, calculations, number identification, and simple arithmetic. This study involved 22 children aged 5-6 years in Kindergarten, Sleman, Special District, Yogyakarta. This study used the quasy experiment method by using the experimental class and control class by giving different treatments. Children who participated in using interactive learning media by using a computer called Kebun Buah media and tested whether they can count various kinds of fruit. The results of research showed that Kebun Buah media affected counting ability on children aged 5-6 years, the results of post-test counting ability of children in the experimental class using Kebun Buah media increased to 88 in average while in the control class using a number card media obtained an average 78.9. This study was conducted by utilizing technology that can increase the implications of education in learning and improving counting ability of early childhood in the use of technological means in the classroom.